Revealing the Physiological Relationship Between Different Blood Groupings And Type II Diabetes - Uddin, Syed Farhan; Waheed, Kiran; Chohan, Habib-ur-Rehman; Ansari, Shafaq (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
OBJECTIVE: To evaluate the association of ABO classification of blood grouping with Type II Diabetes Mellitus. METHODOLOGY: This cross-sectional study was conducted from July to September 2022, in the Department of Physiology of Sindh University Jamshoro Sindh. in collaboration with Diabetic OPD and the Department of Emergency Medicine of Liaquat University Hospital Hyderabad. A total of 360 participants, comprising 220 males and 140 females between 40-60 years participated in this study. Blood groups were tested by glass slide agglutination method using anti-sera A, B, and D. Random blood sugar levels were measured using a Care Sense N Glucometer Model no GM 505 Pad. Data analysis was performed using Graph Pad Prism5, with a significance threshold set at p < 0. 05. RESULTS: This study indicates greater chances of developing Diabetes Mellitus in individuals with Type B group of blood, showing statistical significance in both males (p = 0.02) and females (p = 0.04). In contrast, individuals with blood type A, AB, and O show some degree of protection against the onset of Type II Diabetes Mellitus. CONCLUSION: This study concludes that individuals with blood group B are quite susceptible to the emergence of Diabetes.